Efficiency on the Move: Assessing Operation Management Practices and Developing a Strategic Plan for Bus Companies in a Philippine Provincial District - Velez, Gerard (Journal of Interdisciplinary Perspectives, 2024)
This study assessed bus companies' operation and management practices in a provincial district in the Philippines, focusing on human resource management, facility management, safety protocols, and reservation systems. A descriptive-quantitative approach was employed to gather data from bus personnel, operators, and commuters, providing a comprehensive evaluation of the effectiveness of these practices. The research findings reveal significant operational inefficiencies in bus companies within the provincial district, particularly in safety practices, facility management, and human resource practices. Issues such as the lack of safety tools, poor maintenance schedules, and inadequate training for personnel lead to accidents and poor customer service, while outdated technological practices, like the absence of an online reservation system, further hinder operational effectiveness. Despite bus operators being content with current practices, commuters and personnel express dissatisfaction, highlighting a disconnect between stakeholders. Overall, the study underscores the need for safety, human resources, and facility management improvements to enhance operational effectiveness, customer satisfaction, and business performance. As a result, this study facilitated a collaboration with industry experts to create a comprehensive strategic operations management plan that contains the implementation of robust safety protocols, the establishment of a comprehensive facility management system, continuous staff training programs, the adoption of modern technological solutions, and enhancement of stakeholder communication channels which is progressively adopted by bus companies A, B, and C.